2017
DOI: 10.1016/j.jclepro.2017.06.236
|View full text |Cite
|
Sign up to set email alerts
|

Liquid air/nitrogen energy storage and power generation system for micro-grid applications

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In the rotating blades the flow enters at relative angle ( ) and velocity (w2); next the flow leaves the rotor blade at relative angle ( ) and velocity (w3). as pitch space to chord; aspect ratio (axial cord/blade height); and Reynolds number, as in Equations (13)(14)(15)(16)(17) and stated in [41]:-Where is the blade deflection angle and loss coefficient related to this deflection by the Horlock chart. [41];…”
Section: Preliminary Design By the Mean-line Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the rotating blades the flow enters at relative angle ( ) and velocity (w2); next the flow leaves the rotor blade at relative angle ( ) and velocity (w3). as pitch space to chord; aspect ratio (axial cord/blade height); and Reynolds number, as in Equations (13)(14)(15)(16)(17) and stated in [41]:-Where is the blade deflection angle and loss coefficient related to this deflection by the Horlock chart. [41];…”
Section: Preliminary Design By the Mean-line Methodsmentioning
confidence: 99%
“…In this regard, there has been limited work published on the modeling and optimization of small-scale cryogenic turbines, which are key components of the output power cycle. The efficiency of small expanders is relatively low [14] schemes power recovery plant for nitrogen and air 63.27%, for scheme 2 is 84.15%…”
Section: Cascading Rankine Cycle Hybrid Open-rankine Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that when temperature and pressure increased, the distribution levels of nitrogen became significantly higher as shown in Table 4. There is a possibility of using nitrogen to generate electrical power instead of steam, or nitrogen could be combined with steam to drive the engine of the injection steam generating electrical power as well [42,85].…”
Section: Comparison Of Effectiveness and Properties Of Nitrogen And Steammentioning
confidence: 99%
“…Many researchers have looked into the use of cryogenics as a source of energy for many applications such as cooling for domestic and industrial processes and driving turbines and engines for power generation, etc. [28][29][30][31][32]. Cryogenic energy has also been utilised in freeze desalination by few researchers [14,16,33].…”
mentioning
confidence: 99%